PENERAPAN “PRINSIP NON REFOULEMENT” TERHADAP PENGUNGSI DALAM NEGARA YANG BUKAN MERUPAKAN PESERTA KONVENSI MENGENAI STATUS PENGUNGSI TAHUN - Ismaniar, Titik Juniati; Wija Atmadja, Gede Marhaendra (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013, 2013)
Non refoulement principle is the basis of international protection for the refugees that listed in the Article 33 of the Convention Relating to the Status of Refugees 1951 and therefore binding on all of the states who participating in the convention. This principle prohibits the state to drive the refugees to their homeland where their lives would be endangered. However, it’s often to happen that the state, which is not a party of the 1951 convention, become a destination of the refugees. Therefore, this paper will describe the application of non refoulement principle as the basis of international protection for the refugees and also its implementation on the state that are not the parties in 1951 convention.
Keywords: Non Refoulement, Refugees, the 1951 Convention.